The Effect of Different Inclusion Levels of Corn Starch and Fine Ground Corn With Different Conditioning Temperature or Die Thickness on Pellet Quality - Marut Saensukjaroenphon; Caitlin E. Evans; Cassandra K. Jones; Charles R. Stark; Chad B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2021)
Feeding a greater percentage of whole pellets to poultry and swine provides a greater return on investment for producers. Pellet binders are commonly used in commercial feed mills, but the added cost has limited their use in poultry and swine feed mills. Corn starch could be a potential natural binder for feed as it is for biomass pellet operations. Therefore, the objective of these experiments was to determine the effect of different inclusion levels of corn starch and fine ground corn with different conditioning temperature or die thickness on pellet quality. In, Experiment 1, treatments were arranged in 3 × 2 factorial design of corn starch inclusion level (0%, 5%, and 10%) and die thickness (1/2 in. and 7/8 in.). In Experiment 2, treatments were arranged in 3 × 2 factorial design of fine ground corn inclusion level (0%, 10%, and 20%) and conditioning temperature (175 and 185°F). For Exp. 1, there was a corn starch by die thickness interaction (P = 0.033; Table 3) on pellet durability index (PDI). Increasing concentration of corn starch from 0 to 10% in the diet decreased PDI when diets were pelleted using the ½ in. thick die. However, there was no evidence of difference in PDI when corn starch was increased from 0 to 10% and diets were pelleted using the 7/8 in. die. There was no evidence of an interaction between corn starch inclusion level and die thickness on modified PDI. Increasing die thickness from 1/2 in. to 7/8 in. increased (P = 0.001) modified PDI. There was a linear decrease (P<0.001) in modified PDI as the corn starch inclusion level increased. For Exp. 2, there was no evidence for interaction between fine ground corn inclusion level and conditioning temperature on PDI (P>0.541). There was no evidence of difference in PDI with increasing fine ground corn inclusion. Increasing conditioning temperature from 175 to 185°F increased (P<0.0001) standard and modified PDI. In conclusion, the use of pure corn starch was not an effective binding agent in the feed when the diet contained at least 60% ground corn. The ratio of small corn particles to large corn particles in the diet did not impact pellet quality when the diets were conditioned above 175°F for 35 s and then pelleted with a 5.6 L:D die. Increasing die thickness and conditioning temperature improved pellet quality.
Keywords: conditioning temperature; corn starch; fine corn particles; pellet die; pellet quality; poultry